Combining synergetic control and super twisting algorithm to reduce the active power undulations of doubly fed induction generator for dual-rotor wind turbine system - H. Benbouhenni (National Technical University "Kharkiv Polytechnic Institute", 2021)
Aim. This work presents the amelioration of direct power control using synergetic-super twisting algorithms for asynchronous generators integrated into dual-rotor wind turbine systems. Method. The main role of the direct power control is to control the active and reactive powers and reduce the harmonic distortion of stator current of asynchronous generator for variable speed dual-rotor wind turbine systems. The traditional strategy is more attractive due to its high efficiency and simple algorithm. Super twisting algorithms are a non-linear command strategy; characterized by robustness against the parameters change or disturbances, it gives a good power quality under different conditions such as changing generator parameters. Novelty. Synergetic-super twisting algorithms are designed. Synergetic-super twisting algorithms construction is based on synergetic command and super twisting algorithms in order to obtain a robust control strategy and a fast system with acceptable precision. We use in our study a 1.5 MW asynchronous generator integrated to dual-rotor wind turbine system in order to regulate the active and reactive powers. Results. As shown in the results figures using synergetic-super twisting algorithms the ameliorate performances especially minimizes the torque, active and reactive power undulations, and reduces harmonic distortion of stator current (THD = 0.19 %) compared to traditional strategy.